Meningkatkan Kemampuan Menganalisis Siswa Menggunakan Model Kooperatif Tipe Group Investigation di Siswa Kelas V SD GMIT Kuanino 2 - Lonak, Tri Melinda; Koro, Maxsel; Adoe, Treesly (YASIN, 2025)
This research aims to improve students' analytical skills using the Group Investigation type cooperative learning model in fifth grade students at SD GMIT Kuanino 2. The research method used is a qualitative and quantitative approach (Mix Method). Data collection techniques consisting of observation techniques and test techniques; The research subjects were 21 fifth grade students consisting of 12 male students and 9 female students using qualitative and quantitative data analysis techniques. This research was conducted at SD GMIT Kuanino 2, Kupang City, with the results of this research showing that there was an increase in results in cycle I to cycle II with the average value in cycle I (68.19%) increasing to (81.57%) in cycle II . Of the 21 students, 11 students (52.38%) completed it while 10 students (47.62%) did not complete it. Furthermore, in cycle II of 21 students, 18 students (85.71%) were declared complete, while 3 students (14.29%) did not complete. Based on the research results above, it is concluded that the application of the Group Investigation Type Cooperative Learning Model can improve students' analytical skills.